Matriz cimentícia produzida com resíduo agroindustrial: reação álcali-agregado, ataque por sulfatos e passivação do aço - Rezende, Mariana de Almeida Motta (Universidade Federal de São Carlos, 2019)
The proposal of this research includes the incorporation of residues in concretes and the study of the durability in these concretes with respect to the alkali-aggregate reaction (AAR), to the sulfate attack (SA) and to the passivation of the steel. One of the biggest problems today is the exacerbated generation of solid waste. Within this context, the sugarcane bagasse ash (SBAS) is notable for its high generation rate: for each ton of sugarcane bagasse burned at the mills, about 24 kg of SBAS are generated, which means that in 2017 15 million tons of SBAS were generated in Brazil. In the present study, the AAR, SA and the passive behavior of CA-60 steel were evaluated in reference concrete samples (REF) and samples with 30% SBAS (30SBAS) in bulk substitution to natural sand. To evaluate the AAR, Brazilian standard was followed: samples were exposed to the aggressive solution of sodium hydroxide for 100 days. In this period, expansion measures were carried out and, at the end of this evaluation, it was verified that the SBAS is an aggregate considered potentially innocuous by the norm, as well as the sands used. To evaluate the sulfate attack, Brazilian standard was followed for the external attack and a method adapted to evaluate the internal attack. It was observed that SBAS interferes with the penetration of aggressive solution of sodium sulfate (external attack by sulfates), since mortars with SBAS expanded significantly less than REF. However, the ash did not influence the internal attack by sulfates. To evaluate the passivation, REF and 30SBAS samples were molded, all with two 10 cm steel bars embedded and, in these samples, were carried out the monitoring of open circuit potential, electrochemical impedance spectroscopy and scanning electron microscopy, through which it was verified that the passivating film formed in the steel in a mortar environment with SBAS is more protective than the film formed in the steel in the reference mortar.
Keywords: Concreto; Areia de cinza de bagaço de cana-de-açúcar; Resíduo; Reação álcali-agregado; Ataque por sulfato; Passivação; Concrete; Sugar cane bagasse ash; Residue; Alkali-aggregate reaction; Sulfate attack; Passivation; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL